Can nest design hinder brood parasitism success? - Moreras, Angela; Tolvanen, Jere; Kysučan, Michal; Samaš, Peter; Grim, Tomáš; Thomson, Robert L. (WILEY, 2025)
Avian nest design varies depending on environmental factors but may also be influenced by between-species interactions. In the brood parasitism context, hosts may evolve nest architectures that may limit parasite access to the nest cup, reduce parasite laying success or hinder parasite chick success. Therefore, nest characteristics may reduce the likelihood or minimise the costs of being parasitised. The common redstart Phoenicurus phoenicurus is a regular host of the common cuckoo Cuculus canorus, for which cuckoo eggs are often laid outside the nest cup, resulting in low effective parasitism rates. This allowed us to evaluate variation in host nest design and test whether nest design characteristics correlate with brood parasitism likelihood and cuckoo laying success (i.e. cuckoo egg laid in the nest cup versus outside the nest cup). While recording brood parasitism events in two distant redstart populations, we documented nest cup characteristics, such as internal dimensions, materials used and nest cup position, along with the nest-box dimensions. Cuckoo parasitism likelihood was lower for redstart nests in cavities with smaller entrances, for redstart nests with smaller nest cups and with nest cups that were built level to the rim material. For parasitised nests, cuckoo laying success was lower at redstart nests with nest cups placed further from the cavity entrance. Our results suggest a conditional process, where the cavity entrance size first prevents brood parasites access, then the cup size and the cup level in reference to the rim material affect the cuckoo choice, and finally, the nest cup position hinders cuckoo's laying success. The use of multiple nest design strategies may explain the current low effective parasitism rates in this system. Host nest design may serve as a frontline defence that could shape parasite's preferences, and consequently host nest characteristics.